The Application of Decomposting Microbes For Reduce Amonia and Hydrogen Sulfide Emission From The Piggeries in Bali - Ni Wajan Leestyawati palgunadi; Mirnawati Sudarwanto; Ida Bagus Arka; Eko Sugeng Pribadi (Media Veteriner, 1999)
The unpleasant odor of piggeries is mostly caused by the emission of ammonia and hydrogen sulfide. An experimentwas conducted to study the effect of decomposting microbes EM4 on the emission of ammonia and hydrogen sulfide. The manure was treated with four different concentrations of EM4@, 0'70, 0.5%, 1.0% and 1.5% respectively. The ammonia released was trapped in 0.02N boric acid and analyzed with Nessler method, while the hydrogen sulfide was trapped in 0.02N zinc acetate and analyzed with the methylene blue method. The study suggested that the high concentrationof ammonia and hydrogen sulfide gas were decreasedafter 14 days, and there was no significant differencesin either ammonia or hydrogen sulfide emission although theammonia emission decreased to under 20 ppm with of 1.5%EM^